Effects of CO2 and temperature on the structure and chemistry of C–(A–)S–H investigated by Raman spectroscopy. Issue 77 (17th October 2017) - Ortaboy, Sinem; Li, Jiaqi; Geng, Guoqing; Myers, Rupert J.; Monteiro, Paulo J. M.; Maboudian, Roya; Carraro, Carlo
Abstract : Calcium (alumino)silicate hydrate (C–(A–)S–H) is the critical binding phase in modern Portland cement-based concrete, yet the relationship between its structure and stoichiometry is not completely understood. Abstract : Calcium (alumino)silicate hydrate (C–(A–)S–H) is the critical binding phase in modern Portland cement-based concrete, yet the relationship between its structure and stoichiometry is not completely understood. In this study, Raman spectroscopy is used to analyze the effects of varying Ca/Si molar ratio (0.6–1.6), Al/Si molar ratio (0.0–0.1), and synthesis temperature (7–80 °C) on the chemical composition and atomic configuration of C–(A–)S–H. The experimental results indicate that increasing Ca/Si molar ratio produces less cross-linked C–(A–)S–H structures, while the addition of Al into the system increases the long-range order of its chain-like structure. Furthermore, increasing the synthesis temperature leads to the formation of more polymerized structures, especially in the Al-containing samples. The Raman spectra also suggest the formation of vaterite in C–S–H samples synthesized at low temperatures. Finally, this study reveals that uptake of atmospheric CO2 in C–S–H and C–A–S–H favors the formation of long-range ordered chain-like structures.